DON’T TIP THE SCALES! CARE FOR PATIENTS INVOLVED IN A POLICE INVESTIGATION - Porteous, Joan (Operating Room Nurses Association of Canada Journal, 2005)
Occasionally perioperative nurses are involved in the complex role of caring for medical-legal evidence while also advocating for the patient’s right for privacy. Appropriate management of evidence may be the deciding factor in the outcome of a criminal investigation. Understanding the importance of evidence is the first step in learning how to prevent its unintentional destruction during the surgical procedure.